Finite Element Analysis of Loaded Meshing Characteristic of Spiral Bevel Gear - Deng Yongjun; Zhou Xiang (Jixie chuandong)
Based on the principle of gear meshing,the precise 3 D solid geometry model of spiral gear is established. Then the finite element model of spiral gear for loaded meshing characteristics analysis is built,and the grid size of model is reasonably determined by the Hertz contact theory. Taking six teeth as research objects,the positions of the maximum contact and bending stresses of the spiral gear are found,and the stress curves are plotted in a meshing period. The analysis of meshing characteristics including contact patterns and paths on the gear surface is carried out by selecting the loading condition and assembly error as the variable respectively. The results provide a remarkable guiding role in the design and practical application of spiral bevel gear.